REVERSE LOGISTICS OF PET BOTTLES IN THE COMPANY JZ RECICLAGENS: a case study - Fagundes, Paula Abreu da Silva; Herculani, Rhadler (Revista Interface Tecnológica, 2020)
The present study aimed to research and analyze through a case study the procedures performed in the reverse logistics of the pet bottle material in the company JZ recycling, located in the city of Bebedouro, SP. Using quantitative methods of production for four months. Specifying part of the pet material logistical procedures, among them the purchase and transportation, separation, storage and compaction of the same, taking into account that they are only part of the general reverse logistics processes for this waste. After analyzing the polymeric compound PET (polyethylene terephthalate), it was noted that a seasonality in December with the entry of pet waste in the company and consequently a period of production of the material in the month of January. It was concluded that, for reverse logistics of pet bottle, it is neessary many kinds of procedures, however, it could be possible analyses some of these in the real case study.